Improving Students' English Speaking Skills Through Collaborative Learning at Anastasya School Medan - Silaban, Roikestina; Sihombing, Faija; Panjaitan, Tulus JT.; Silaban, Lidia; Ginting, Melda Oktika (Dedikasi Sains dan Teknologi (DST), 2025)
Speaking is one of the most essential skills for students to master in facing the challenges of globalization and the era of international communication. However, in reality, many students at Anastasya School Medan struggle to express their ideas orally in English due to limited practice, low self-confidence, and the dominance of individualistic teaching methods. In response to this issue, this community service program was carried out with the aim of improving students’ speaking skills through a collaborative learning approach. The activities were conducted in the form of interactive training and paired or group conversation simulations using daily topics relevant to the students' real-life context. Documentation of the activities indicated high student enthusiasm and significant improvement in vocabulary mastery, pronunciation, and speaking fluency. Observations and evaluations revealed that 80% of participants showed increased scores in speaking aspects after participating in the program. Furthermore, students reported feeling more confident and motivated to speak English through collaborative learning. In conclusion, collaborative learning has proven to be an effective method for enhancing students’ speaking abilities by promoting active interaction, teamwork, and a supportive learning atmosphere. This model can be adopted by other schools facing similar challenges.